Application of Navigated Ultrasound for Assessment of the Anterior Pelvic Plane in Patients With Degenerative Hip Diseases. (8th April 2017) - Kochman, Andrzej; Goral, Adrian; Martin, Tobias; Marek, Wojciech; Kozak, Josef; Morawska‐Kochman, Monika; Synder, Marek
Abstract : Objectives: Correct positioning of the acetabular cup is the key for successful total‐hip replacement. In common clinical practice, the target alignment of the cup is defined with respect to the anterior pelvic plane. In patients with substantial anterior pelvic plane inclination, this condition may lead to inappropriate distribution of the load on the cup, as most of the forces exerted within the hip joint act along the vertical axis. With the known pelvic inclination, it is possible to readjust the position of the cup with respect to the individual posture of the patient. In this work, we present the first clinical evaluation of a new approach to measurement of the pelvic tilt angle using navigated ultrasound. Methods: In our method, the ultrasound probe is tracked with an optical localizer implemented on a handheld mobile device. The method was tested by taking preoperative measurements from 20 patients with osteoarthritis in standing, sitting, and supine positions. Results: The mean values of the measured angles were consistent with the corresponding results reported by other authors. Conclusions: Considering the noninvasiveness of the method and affordability of the hardware used in our system, it can be used in preoperative and postoperative measurements of pelvic orientation for supporting surgery planning and evaluation of treatment outcomes.